TRANSAKSI KEUANGAN DERIVATIF LINDUNG NILAI (HEDGING) PADA PT. ASTRA INTERNATIONAL TBK - Hariko Wayra; Siti Rodiah (Jurnal Akuntansi dan Manajemen Bisnis, 2023)
Based on research conducted by the Journal of Management and Business, hedging is an action to protect companies from the risk of loss of foreign exchange rates that occur due to business transactions, so that companies can conduct business transactions with a number of foreign currenciesto avoid the risk of foreign exchange losses that occur due to business transactions carried out by companies using derivative instruments (Adrian Sutedi in Desmiza, 2015). With derivative instruments, companies can minimize the possibility of bankruptcy, making it easier for a company to be able to get loans with lower interest rates (because the risk obtained by lenders is lower) (Zahra &; Tjahjono, 2020). As for the purpose of doing this research is to find out how the use of hedging applied by PT. Astra International Tbk uses financial derivative instruments from the 2022 annual financial reports. The method used by researchers in this study is a qualitative method with a content analysis approach.The results of this study researchers found that PT. Astra International Tbk uses several hedging derivative financial transactions, such as cross currency swaps, interest rate swaps, commodity contracts and foreign exchange futures contracts. Of the four types of hedging derivative instruments, PT. Astra International Tbk classifies these instruments into cash flow hedges that comply with the hedge accounting objective criteria and cash flow hedge categories that do not comply with the hedge accounting objective criteria.